Chronic Lymphocytic Leukemia Involving the Liver Without High-Grade Transformation - Alexandra V. Kimchy; William D. Davis; Megan E. Murphy; Melinda G. Fang; Annie J. Kruger; James H. Lewis (Annals of Internal Medicine: Clinical Cases)
Chronic lymphocytic leukemia is most frequently encountered among the elderly population. Hepatic infiltration may be present at the time of diagnosis, but significant extranodal involvement rarely occurs without high-grade transformation. Abnormal liver enzymes have important prognostic implications in terms of staging the disease and initiating treatment. We describe an atypical presentation of chronic lymphocytic leukemia in a patient who presented with rising liver enzyme levels, extensive hepatic infiltration, and portal hypertension but with no evidence of high-grade transformation on liver biopsy.